2009
DOI: 10.1089/apc.2009.0036
|View full text |Cite
|
Sign up to set email alerts
|

Changes in At-Risk Behavior for HIV Infection among HIV-Positive Persons in Italy

Abstract: Many HIV-positive persons reportedly continue to engage in at-risk behavior. We compared the sexual and drug-using practices of HIV-positive persons before and after the diagnosis of HIV infection to determine whether their behavior had changed. To this end, in 2006, we conducted a cross-sectional study involving clinical centers in five Italian cities. Each center was asked to enroll 100 persons aged 18 years or older who had a diagnosis of HIV infection that dated back at least 2 years. Data were collected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Indeed, as noted in previous research, after an HIV diagnosis, many persons forego practices that transmit HIV and become less infectious as a result of medication (Sasse et al 2006;Charlebois et al 2005;Fox et al 2009;Camoni et al 2009;Marks et al 2006). While the association between HIV-positive status awareness and decreased HIV transmission has led some authors to argue that HIV testing services should be as inclusive as possible, it is important to emphasize that the behaviour changes which occur after an HIV diagnosis are similar when HIV testing is done anonymously or with people's names (Marks et al 2005(Marks et al , 2006Sasse et al 2006;Charlebois et al 2005;Osmond et al 1999;Fox et al 2009;Camoni et al 2009). The group that Lyon (2007) called 'the watched' thus actively participates in their own surveillance by voluntarily seeking out, and subsequently undergoing, HIV testing, and then by reducing the possibility of onward HIV transmission through behaviour change and viral load suppression.…”
Section: Formal and Informal Hiv Surveillancementioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, as noted in previous research, after an HIV diagnosis, many persons forego practices that transmit HIV and become less infectious as a result of medication (Sasse et al 2006;Charlebois et al 2005;Fox et al 2009;Camoni et al 2009;Marks et al 2006). While the association between HIV-positive status awareness and decreased HIV transmission has led some authors to argue that HIV testing services should be as inclusive as possible, it is important to emphasize that the behaviour changes which occur after an HIV diagnosis are similar when HIV testing is done anonymously or with people's names (Marks et al 2005(Marks et al , 2006Sasse et al 2006;Charlebois et al 2005;Osmond et al 1999;Fox et al 2009;Camoni et al 2009). The group that Lyon (2007) called 'the watched' thus actively participates in their own surveillance by voluntarily seeking out, and subsequently undergoing, HIV testing, and then by reducing the possibility of onward HIV transmission through behaviour change and viral load suppression.…”
Section: Formal and Informal Hiv Surveillancementioning
confidence: 82%
“…Indeed, in determining if an HIV diagnosis corresponds with changes in sexual and drug-using practices, Camoni and others (2009) found that their participants reported the following changes after their HIV diagnosis: a significant decrease in their number of different sexual partners; a significant decrease in commercial sex (as client or worker); and a significant increase in condom use with both casual and regular sexual partners. Additionally, the participants reported a significant decrease in the use of all drugs following their HIV diagnoses (Camoni et al 2009). …”
Section: Hiv Status Awareness and Decreased Transmissionmentioning
confidence: 99%
“…This has been documented in studies analyzing the risk of STIs among HIV-positive individuals. 25,26 Thorough risk assessment and review of medical history are crucial to ensure that individuals with a previously diagnosed STI are identified by health care providers and prioritized for prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, behavioral analysis made before and after HIV diagnosis has allowed for identifying late testers as tending to reduce sexual relations with steady or occasional partners while non-late testers only reduce sex with occasional partners but increase condom use in all sexual practices. However, the proportion of people who continue not using condoms is still high (Sudarshi et al, 2008;Camoni et al, 2009). It must be stressed that the importance of this result is limited by the low number of answers provided by the late testers in this part of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%